Unveiling transthyretin cardiac amyloidosis and its predictors among elderly patients with severe aortic stenosis undergoing transcatheter aortic valve replacement. (1st August 2017) - Castaño, Adam; Narotsky, David L; Hamid, Nadira; Khalique, Omar K; Morgenstern, Rachelle; DeLuca, Albert; Rubin, Jonah; Chiuzan, Codruta; Nazif, Tamim; Vahl, Torsten; George, Isaac; Kodali, Susheel; et al.
Abstract: Aims: Transthyretin cardiac amyloidosis (ATTR-CA) has been reported in patients with aortic stenosis (AS) but its prevalence and phenotype are not known. We examine elderly patients with severe symptomatic AS undergoing transcatheter aortic valve replacement (TAVR) and determine the prevalence and phenotype of ATTR-CA non-invasively. Methods and results: We performed technetium-99m pyrophosphate ( 99m Tc-PYP) cardiac scintigraphy prospectively on patients who underwent TAVR, to screen for ATTR-CA. Transthoracic echocardiography and speckle-strain imaging were performed. We assessed the association of several parameters with ATTR-CA using multivariable logistic regression and constructed receiver operating curves to evaluate the best predictors of ATTR-CA. Among 151 patients (mean age 84 ± 6 years, 68% men), 16% ( n = 24) screened positive for ATTR-CA with 99m Tc-PYP scintigraphy. Compared with patients without ATTR-CA, ATTR-CA patients had a thicker interventricular septum (1.3 vs. 1.1 cm, P = 0.007), higher left ventricular (LV) mass index (130 vs. 98 g/m 2, P = 0.002), and lower stroke volume index (30 vs. 36 mL/m 2, P = 0.009). ATTR-CA patients had advanced diastolic dysfunction with higher E / A ratio (2.3 vs. 0.9, P = 0.001) and lower deceleration time (176 vs. 257 ms, P < 0.0001); impairment in systolic function with lower ejection fraction (48% vs. 56%, P = 0.011), myocardial contraction fraction (26 vs. 41, P < 0.0001), and average of lateral and septal mitral annular tissue Doppler S' (4.0 vs. 6.6 cm/s, P < 0.0001). While ATTR-CA patients had more impaired global longitudinal strain (−12 vs. −16%, P = 0.007), relative apical longitudinal strain was the same regardless of ATTR-CA diagnosis (0.98 vs. 0.98, P = 0.991). Average S' best predicted ATTR-CA in multivariable logistic regression (odds ratio 16.67 per 1 cm/s decrease with AUC 0.96, 95% confidence interval 0.90–0.99, P = 0.002) with a value ≤6 conferring 100% sensitivity for predicting a positive 99m Tc-PYP amyloid scan. Conclusions: Transthyretin cardiac amyloidosis is prevalent in 16% of patients with severe calcific AS undergoing TAVR and is associated with a severe AS phenotype of low-flow low-gradient with mildly reduced ejection fraction. Average tissue Doppler mitral annular S' of < 6 cm/s may be a sensitive measure that should prompt a confirmatory 99m Tc-PYP scan and subsequent testing for ATTR-CA. Prospective assessment of outcomes after TAVR is needed in patients with and without ATTR-CA.